System of automated monitoring and forecasting of the remaining resource of pipeline transport - S. O. Gaponenko; А. E. Kondratiev; M. V.. Kalinina; R. V. Akhmetova (Известия высших учебных заведений: Проблемы энергетики)
This article presents a system of automated monitoring and forecasting of the residual resource of pipeline transport, consisting of a developed and manufactured information and diagnostic complex for monitoring the technical condition of pipeline transport and software. Informative frequency ranges for monitoring the technical condition of pipeline transport are determined. Experimental studies have been conducted to confirm the effectiveness of the developed technical solution. The paper considers the problems of reliability of pipeline transport. The analysis of existing methods for assessing the technical condition of pipelines is carried out. A system of automated monitoring and forecasting of the residual resource of pipeline transport has been developed. Experimental studies have been conducted. The methods of circuit and simulation modeling, the theory of automatic control, experimental planning, decision-making, probabilistic and statistical methods of mathematical processing and the method of finite element analysis were used in the performance of the work. Based on the resultsof the study, a new methodology for assessing the technical condition of pipeline transport has been developed.